Prevalence and determinants of violence against healthcare workers in multiple settings: a cross sectional study - Jackson, Preetha; Bijoy, Hanna; P. V., Gopika; Anoop, Hanna Elsa; Nair, Gadha Jayachandran; Jose, Flemin; V. R., Reshma; Viswan, Leena; Mani, Sapna Meryl; Johns, Felix (International Journal Of Community Medicine And Public Health, 2024)
Background: The quality of clinical care hinges on the doctor-patient relationship. The murder of Dr. Vandana Das highlights the urgent need to address violence against healthcare workers (HCWs). This study aimed to ascertain the prevalence of violence among HCWs, examine reporting mechanisms, and comprehend the repercussions of such incidents. Methods: A cross-sectional study was conducted among HCWs at Pushpagiri Medical College Hospital and Taluk headquarters hospital, Pulinkunnu. A semi-structured questionnaire derived from surveys on workplace violence in the health sector by PSI (Public Services International), ILO (International Labour Office), ICN (International Council of Nurses), and WHO was used to measure violence. Results: Among 185 participants, 150 were from private settings and 35 from government settings. In government settings, 14.3% experienced physical violence, and 31.4% faced verbal violence. In private settings, 9.3% encountered physical violence, 39.3% experienced verbal violence, and 2.7% reported sexual harassment. Incidents of physical violence were more frequent among HCWs with 6-10 years of experience and those working with adult patients. Verbal violence was more common among staff working in shifts and with adult and elderly patients. Conclusions: Verbal violence was the most prevalent, affecting 37% of HCWs, often from patients’ relatives or bystanders. Contributing factors included staff shortages, patient non-compliance, long waiting times, communication issues, and work overload. Addressing violence against HCWs requires improved staffing, communication, security measures, and stringent legislation to safeguard HCWs’ well-being and patient care quality.